Effect of sperm concentration on fertilization rate and the timing of early developmental stages of Imbaw, Anodontia edentula. - Arboleda, Erika Anfone (1999.)
In this study, effect of sperm concentration to fertilization rate is investigated. Also, the timing of early developmental stages is done. Sperm concentration at seventy is most effective although not significantly different. In the range used, effect of sperm concentration to fertilization rate is broad. The concentration of ten sperm per egg is least effective and significantly different from all the rest. In developmental stages, polar body extrusion is observed after ten minutes from fertilization. Two-cell and four-cell is formed within an hour. After two hours, eight-cell and sixteen-cell stage is noted. The larval stage trocophore is already present after the fifteenth hour. The straight-hinge veliger can be observed after twenty four hours.
Thesis (Undergraduate, Bachelor of Science in Biology) College of Arts and Sciences, University of the Philippines in the Visayas, Iloilo City.
Keywords: Imbaw; Anodontia Edentula